2022
DOI: 10.4102/sajpsychiatry.v28i0.1700
|View full text |Cite
|
Sign up to set email alerts
|

Experience of violence, coping and support for nurses working in acute psychiatric wards

Abstract: Background: Acute psychiatric wards are stressful working environments because of the nature of the mental illness of patients admitted. These patients present with a variety of complex psychiatric problems and social control that require skilled and competent nurses to manage them. The shortage of nurses, especially with advanced psychiatric qualifications or necessary experience, may create challenges for nurses as they navigate this stressful working environment.Aim: The aim of this study was to explore and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Similar to other studies (Bekelepi & Martin 2022 :3; Harris et al 2015 :134), the findings of this study confirm that male psychiatric nurses exposed to violence perceive the environment as unsafe. This experience made them fearful when caring for state patients (Bekelepi & Martin 2022 :4).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to other studies (Bekelepi & Martin 2022 :3; Harris et al 2015 :134), the findings of this study confirm that male psychiatric nurses exposed to violence perceive the environment as unsafe. This experience made them fearful when caring for state patients (Bekelepi & Martin 2022 :4).…”
Section: Discussionsupporting
confidence: 92%
“…A fair number of qualitative studies on the experience of violence in maximum-security forensic units exist (Dickens et al 2013 :532–544; Harris et al 2015 :130–138). While most studies have reported on the incidence and physical impact of violence in forensic units, fewer studies have adequately explored the psychological impact thereof (Bekelepi & Martin 2022 :3; Lantta et al 2016 :2; Odes et al 2021 :28). There has been no primary focus on male psychiatric nurses and violence experienced in maximum-security forensic units in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in their studies Joubert and Bhangwan (2018) recommended developing a psychiatric training programme to address the identified challenges of non‐psychiatric nurses. However, Timor and Suryani Sutini (2019) and Bekelepi and Martin (2022) reported that some nurses expressed their need for psychiatric emergency training to master the technique of dealing with acute psychiatric people. It could reduce the risk of injury when faced with people who display violent behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…In-service training is carefully organized and is part of ongoing education(Booyens & Bezuidenhout, 2015).Similarly, in their studiesJoubert and Bhangwan (2018) recommended developing a psychiatric training programme to address the identified challenges of non-psychiatric nurses. However,Timor and Suryani Sutini (2019) andBekelepi and Martin (2022) reported that some nurses expressed their need for psychiatric emergency training to master the technique of dealing with acute psychiatric people.It could reduce the risk of injury when faced with people who display violent behaviour.As a result,Heim et al (2020) noted that non-psychiatric nurses lacked training in specialized clinical and communication skills, except for one study that showed a favourable impact of interview skills training on attitudes. However,Timor and Suryani Sutini (2019) support these findings to ensure patient safety and high-quality treatment by stating that the primary goal of nursing education is to give nursing professionals the required level of competency.…”
mentioning
confidence: 99%
“…Sadly, nurses were not immune to death as high mortality rates were reported across the globe during COVID-19 in both developing and developed countries (Vera-Alanis et al, 2022). In a South African context with a shortage of qualified nurses, it becomes important to support student nurses (Bekelepi & Martin, 2022;Malatji et al, 2022). Student attrition and poor progression significantly affect the country's planned nursing and midwifery workforce projections (Mudlaly & Mtshali, 2018).…”
Section: Introductionmentioning
confidence: 99%